Making decisions about fertility: Three facts GPS need to communicate to women - Mazza, D.; Cannold, L.; Nagle, C.; McKay, F.; Brijnath, Bianca (The Royal Australian College of General Practitioners, 2012)
Background: Average annual fertility rates in industrialised countries have been below two children per woman for the past 3 decades. The reasons behind women's childbearing behaviour are complex. However, a lack of awareness regarding the consequences of delayed childbearing and the inability of reproductive technologies to overcome the 'biological clock' may be contributory factors. Objective/s: A narrative review guided by the research question: What do women need to know about the consequences of delayed childbearing in order to make informed decisions about their fertility? Discussion: There are three facts that women need to know in order to make informed decisions around their fertility: Some women want to have more children than they are able to have because they postpone childbearing; there can be medical consequences to delaying childbearing and; some women's ideas about their fertility don't match the 'the scientific facts'. General practitioners are well placed to play a strategic role in the provision of timely, relevant information to help women make informed decisions about their fertility. Further research is needed to identify the most appropriate ways for GPs to communicate this information.